METHODOLOGICAL CHALLENGES IN THE USE OF THE INTERNET FOR SCIENTIFIC RESEARCH: TEN SOLUTIONS AND RECOMMENDATIONS - REIPS, ULF-DIETRICH; BUCHANAN, TOM; KRANTZ, JOHN; MCGRAW, KEN (Studia Psychologica: Theoria et praxis, 2015)
Researchers, editors, and other players in the scientific community have shown and continue to show high interest in and great enthusiasm for Internet-based research methods. However, methodological research has indicated that there are a number challenges that online researchers must consider. In this article, we provide information about solutions to ten common obstacles in Internet-based research. These are: Repeat or multiple submissions, comparisons between modes, reporting demographics of Internet participants, achieving compatibility for samples when Web and lab samples methods are to be compared, persistency of instrument, international nature of the Internet, possible confounds arising from recruitment techniques, reliance on a single Website or recruitment method to attract participants, dropout and other types of nonresponse, and the preconception that Internet samples invariably lead to different results.